MATHEMATICS CUT OF SCORE WITH STANDARD SETTING ANGOFF METHOD - Hairun, Yahya (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2015)
This study  aims to find out of cut of score of mathematics with standard setting based on  Angoff method. The research was conducted in SMP at Ternate. The subject of this research was 11 mathematics teacher. The research  was description method with standard setting based Angoff method procedure. The instrument was mathematics item pool of  yunior high school nation examanition. The research result shows: (1)  the minimum ability with standard setting Angoff method is high, and (2)  cut of score Angoff method is 67.5. Panelist precentation score of Angoff method 66 percent.